BANK CREDIT ACCESSIBILITY AND PERFORMANCE OF SMES IN KWARA STATE, NIGERIA: A PLS-SEM ANALYSIS - Sanni, Mubaraq; Oke, Lukman Adebayo; Alayande, Idayat Titilayo (Copernican Journal of Finance & Accounting, 2020)
This study examines the effect deposit money banks credit accessibility on SMEs performance in Kwara State, Nigeria. The population of the study consists of three hundred and eighty-two (382) respondents and one hundred and ninetyeight (198) were randomly selected as the sample size of the study. Data were drawn from the primary source to elicit responses from SME owners/managers. Descriptive statistics and Partial least square - Structural Equation Model (PLS-SEM) estimation techniques were employed to analyse the data collected. The study revealed that deposit money banks credit accessibility has a positive significant effect on SME performance (T=10.795, β=0.043) at 5% significance level and credit related charges (interest) also has a positive significant effect on SME performance (T=10.690, β =0.458). This implies that provision of finance by deposit money banks at relatively low cost play an important role in boosting the performance of SMEs. The study therefore concluded that SMEs in Kwara State are faced with the problem of access to finance as they are not fully benefiting from the credit facilities of the deposit money banks. The study therefore recommended that deposit money banks should put in place a more SME friendly credit administration system for SMEs to enable them access fund easily and affordably.